Lithium nickel borides: evolution of [NiB] layers driven by Li pressure. Issue 7 (22nd December 2020) - Gvozdetskyi, Volodymyr; Sun, Yang; Zhao, Xin; Bhaskar, Gourab; Carnahan, Scott L.; Harmer, Colin P.; Zhang, Feng; Ribeiro, Raquel A.; Canfield, Paul C.; Rossini, Aaron J.; Wang, Cai-Zhuang; Ho, Kai-Ming; et al.
Abstract : Insertion of additional Li atoms into the Li-monolayer in the structures of layered LiNiB polymorphs induces the deformation of [NiB] layers and alters their stacking, however, does not affect magnetic properties. Abstract : Here we show the effect of Li chemical pressure on the structure of layered polymorphs with LiNiB composition: RT -LiNiB (room temperature polymorph) and HT -LiNiB (high temperature polymorph), resulting in stabilization of the novel RT -Li1+ x NiB ( x ∼ 0.17) and HT -Li1+ y NiB ( y ∼ 0.06) phases. Depending on the synthesis temperature and initial Li content, precisely controlled via hydride route synthesis, [NiB] layers undergo structural deformations, allowing for extra Li atoms to be accommodated between the layers. In situ variable temperature synchrotron and time-dependent laboratory powder X-ray diffraction studies suggest Li step-wise deintercalation processes: RT- Li1+ x NiB → RT- LiNiB (high temp.) → LiNi3 B1.8 → binary Ni borides and HT -Li1+ y NiB → HT -LiNiB (high temp.) → LiNi3 B1.8 → binary Ni borides. Quantum chemistry calculations and solid state 7 Li and 11 B NMR spectroscopy shed light on the complexity of real superstructures of these compounds determined from high resolution synchrotron powder diffraction data.